The Determinants of Students' Intentions to Use Artificial Intelligence-Based Mobile Investment Apps - Pusposari, Devy; Rachman, Oktarian Aulia; Kusumadewi, Areta Widya (The International Journal of Accounting and Business Society, 2024)
Purpose—This study investigated the determinants of students' intentions to use Artificial Intelligence-based Mobile Investment Apps known as Robo Advisors. Perceived ease of use, perceived usefulness, and perceived trust are the presumed determinants of students' intentions, directly and indirectly mediated by perceived attitudes. Design/methodology/approach —  The study employs a survey of 231 students of the Accounting Departments of Universitas Brawijaya, analyzed by the Partial Least Square method. Findings—The study's results revealed that the students’ intentions were directly affected by perceived usefulness and perceived attitudes, and perceived attitudes were affected by perceived ease of use, usefulness, and trust. Practical implications —  This finding implies that app developers should improve their app features and interactions with students to develop perceived ease of use and perceived trust. Originality/value—This study combines the Technology Acceptance Model and Theory of Trust to provide a firmer model for explaining students' intentions. Keywords —  Robo Advisor, mobile investment apps, Artificial Intelligence, investment, TAM. Paper type —  Research Paper